2016
DOI: 10.1111/1365-2745.12590
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation to controlling new microbial epibionts in the invaded range promotes invasiveness of an exotic seaweed

Abstract: Summary Rapid adaptation to novel biotic interactions and abiotic factors in introduced ranges can be critical to invasion success of both exotic terrestrial and aquatic plants. Seaweeds are extremely successful biological invaders in marine environments. Along with herbivores, foulers − ubiquitous enemies in the marine environment − have the potential to determine the success or failure of invasive seaweeds. However, research on the topic of rapid adaptation of seaweeds to biotic challenges is still in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 75 publications
(151 reference statements)
1
48
1
Order By: Relevance
“…However, it gives the first evidence that the capacity to defend against epibionts is higher in non-native individuals than in nativeregardless of whether the epibionts originate from the native of the non-native range of G. vermiculophylla. Our findings, therefore, seemingly contradict the observations made by Saha et al (2016), who focused on seaweed-bacteria interactions and showed that non-native G. vermiculophylla are better defended against bacterial epibionts from the non-native range but, at the same time, have reduced their capacity to defend themselves against epibionts from their home range. The contradiction may be due to the use of different micro-epibionts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, it gives the first evidence that the capacity to defend against epibionts is higher in non-native individuals than in nativeregardless of whether the epibionts originate from the native of the non-native range of G. vermiculophylla. Our findings, therefore, seemingly contradict the observations made by Saha et al (2016), who focused on seaweed-bacteria interactions and showed that non-native G. vermiculophylla are better defended against bacterial epibionts from the non-native range but, at the same time, have reduced their capacity to defend themselves against epibionts from their home range. The contradiction may be due to the use of different micro-epibionts.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study is the second biogeographical comparison of defence capacities against epibionts between native and non‐native populations of G. vermiculophylla (Saha et al . ), which is now invasive in many coastal areas world‐wide. However, it gives the first evidence that the capacity to defend against epibionts is higher in non‐native individuals than in native – regardless of whether the epibionts originate from the native of the non‐native range of G. vermiculophylla .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other studies that use clonal propagation (e.g., Galloway, ), the consistency in phenotypic responses across field‐collected and common‐garden thalli indicates that population‐level differences likely have a genetic basis, but does not preclude a role for environmental history, phenotypic plasticity, or both. We note that previous studies of population‐level differentiation in G. vermiculophylla phenotypes (Hammann, Wang, Boo, Aguilar‐Rosas, & Weinberger, ; Hammann et al., ; Saha, Wiese, Weinberger, & Wahl, ; Wang et al., ) assayed populations that were not within the source region and thus could not separate prior adaptation from the signal of rapid evolution during the invasion that we infer here.…”
Section: Discussionmentioning
confidence: 67%
“…To quantify the antifouling activity of eelgrass surface extracts, we used the anti-bacterial-settlement bioassay described in [41] and [23]. Bacterial isolates applied in these bioassays had been isolated previously from stones of the North Sea and Baltic Sea upper subtidal and lower intertidal zones [42] and had been conserved in −80 • C. Four bacterial isolates were used in the assays. They were Alteromonas stellipolaris (strain AMAN1), Loktanella rosea (strain AFALK1), Polaribacter dokdonensis (strain ANORD1), and Bacillus aquamaris (strain AMAN10) [42].…”
Section: Methodsmentioning
confidence: 99%